Martin Luther King, Jr., papers - King, Martin Luther, Jr., 1929-1968.; King, Coretta Scott, 1927-2006.
Twelve speeches delivered by King, including a typescript of his "I have a dream" speech given at the 1963 March on Washington for Jobs and Freedom and a photocopy of the copyright registration form for it. Also includes speeches on civil rights for African Americans delivered at Holt Street Church, Montgomery, Ala., 1955; Sixteenth Street Baptist Church, Birmingham. Ala., May 3, 1963; and on various occasions in Atlanta, Ga., Chicago, Ill., Frogmore, S.C., New York, N.Y., and Philadelphia, Pa. Also includes transcripts of three speeches (1969) delivered by Coretta Scott King in Washington, D.C., relating to the Vietnam Conflict. Transcripts are stamped with the dates the speeches were registered for copyright.
Typewritten transcripts and photocopies. [S.l.].
Clergyman and civil rights leader.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Holt Street Baptist Church (Montgomery, Ala.); Sixteenth Street Baptist Church (Birmingham, Ala.); African Americans -- Civil rights; Baptists -- Alabama; Vietnam War, 1961-1975 -- Public opinion; Public opinion -- United States; Atlanta (Ga.) -- History -- 20th century; Birmingham (Ala.) -- History -- 20th century; Chicago (Ill.) -- History -- 20th century; Frogmore (S.C.) -- History -- 20th century; Montgomery (Ala.) -- History -- 20th century; New York (N.Y.) -- History -- 20th century; Philadelphia (Pa.) -- History -- 20th century; Washington (D.C.) -- History -- 20th century; Civil rights leaders; Clergy